Etiology and outcomes of anuria in acute kidney injury: a single center study - Hye Min Choi; Sun Chul Kim; Myung-Gyu Kim; Sang-Kyung Jo; Won Yong Cho; Hyoung Kyu Kim (The Korean Society of Nephrology, 2015)
Background: It was previously known that anuric acute kidney injury (AKI) is uncommon and its occurrence suggests complete ureteral obstruction, shock, or a major vascular event. As the epidemiology of AKI has significantly changed over the past decade, it is possible that the incidence, etiology, or clinical characteristics of anuric AKI have also changed. Methods: A prospective cohort study was conducted that included all patients undergoing renal replacement therapy (RRT) for AKI during a 2-year period in a tertiary hospital. Patients were classified as having anuric, oliguric, or nonoliguric AKI based on their volume of urine when RRT started using the modified Acute Kidney Injury Network criteria. Results: Of the 203 patients included in the study, 21.2% met the criteria for anuric AKI. Septic and postoperative AKI were the main causes of anuric AKI, with 60.5% of incidences occurring in hospital. Anuric AKI was associated with a younger age, a lower prevalence of pre-morbid chronic kidney disease and diabetes, more frequent continuous RRT requirement, and multi-organ dysfunction. In addition, patients with anuric AKI had a higher rate of in-hospital mortality and long-term dependence on RRT than patients with nonanuric AKI. Conclusion: Anuric AKI is common, with sepsis as the main etiological insult, and is associated with adverse outcomes among patients with AKI who require RRT.